Evaluasi Penggerak Mesin Pengolahan Tandan Kosong (EFB) dengan Menggunakan Motor Induksi di PT. Suryabumi Argo Langgeng Sumatra Selatan - Andiko Andiko; M. Saleh Al Amin; Perawati Perawati; Yudi Irwansi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The research issues include the performance of three-phase induction motors and the impact of load on three-phase induction motors. This study aims to develop a driving system for empty fruit bunches (EFB) processing machines using induction motors at PT. Suryabumi Agro Langgeng, South Sumatra. The research was conducted at PT. Suryabumi Agro Langgeng in South Sumatra, from May to June 2024. Primary data in this research were obtained through observation and interviews, while secondary data were gathered from document analysis. In the context of this research on three-phase induction motors, document analysis techniques can be used to analyze various documents such as scientific literature, technical specifications, maintenance reports, production records, or other documents related to induction motors. The research methods include system requirements analysis, system design and implementation of the driving system, and performance testing of the developed system. The results show that the use of induction motors can provide better operational efficiency in EFB processing. This research is expected to contribute positively to improving the efficiency and productivity of PT. Suryabumi Agro Langgeng's operations.